2014
DOI: 10.1002/jcph.342
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double blinded, placebo‐controlled trial to evaluate the efficacy and safety of tolvaptan in Chinese patients with hyponatremia caused by SIADH

Abstract: To study the effect of tolvaptan on non-acute, non-hypovolemic hyponatremia in inappropriate secretion of antidiuretic hormone (SIADH) syndrome in Chinese patients. Hyponatremic SIADH patients received placebo (N = 18) or tolvaptan (N = 19) at an initial dose of 15 mg/day with further titration to 30 mg/day and 60 mg/day based on serum sodium concentrations. Randomized, double-blind, placebo-controlled trial. Primary endpoint was the change of the serum sodium from baseline to days 4 and 7. Analysis of covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…The trials at day 30 showed high levels of heterogeneity ( I 2 = 74%). Results were similar for tolvaptan compared to placebo when considering SIADH population/subgroups only at day 4 …”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The trials at day 30 showed high levels of heterogeneity ( I 2 = 74%). Results were similar for tolvaptan compared to placebo when considering SIADH population/subgroups only at day 4 …”
Section: Resultsmentioning
confidence: 78%
“…Two trials assessed conivaptan, 13,14 four assessed lixivaptan, [15][16][17][18] three assessed satavaptan [19][20][21] and nine assessed tolvaptan. [22][23][24][25][26][27][28][29] There were no RCTs published assessing other known interventions such as urea, sodium tablets or mannitol. We contacted the authors of ten studies and Otsuka, to seek additional information about the trials' design and outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trials assessed conivaptan, 13,14 four assessed lixivaptan, [15][16][17][18] three assessed satavaptan [19][20][21] and nine assessed tolvaptan. [22][23][24][25][26][27][28][29] There were no RCTs published assessing other known interventions such as urea, sodium tablets or mannitol. We contacted the authors of ten studies and Otsuka, to seek additional information about the trials' design and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Some trials reported data for a specific population and others included patients with various underlying causes. Three trials assessed hyponatraemia in patients with SIADH, 15,21,22 four assessed hyponatraemia in patients with congestive heart failure, [24][25][26][27] two assessed hyponatraemia in patients with cirrhosis, 17,20 and one assessed hyponatraemia in patients with cancer. 28 The other eight trials assessed hyponatraemia in patients with a range of underlying conditions.…”
Section: Resultsmentioning
confidence: 99%